Technology issues in the energy sector of developing countries : small-scale hydropower projects in Nepal : study - Shrestha, Kedar L.; Sharan, Harendra N.; Head, Chris R.; United Nations Conference on Trade and Development. Secretariat ([Document] / United Nations, 1987)
Summary and conclusions (s. 33-35).
Keywords: energia : Nepal; voimatalous : Nepal